KANDUNGAN KARBOHIDRAT BUAH ALPUKAT CIPEDAK BERDASARKAN NILAI ABSORBANSI DENGAN MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Berlianti, Nindha Ayu; Nikmah, Tia Frida Khoirun; Misto (Jurnal Penelitian Sains dan Teknologi Indonesia, 2023)
Avocados are one of the important fruit commodities in the world because they have quite high nutritional content. Indonesia is the country with the 5th largest avocado cultivation in the world. Cipedak avocados have recently become popular in cultivation among Indonesian people because they have the advantage of sweet and sticky fruit texture, short productivity, and also their medium size of around 400-600 grams. Avocados have bioactive components such as vitamin C, protein, fiber and carbohydrates. Carbohydrates are the main source for the human body. Carbohydrates contribute 4 kcal. This research aims to measure carbohydrate levels in half-ripe and ripe Cipedak avocados, because the fruit ripening process results in changes in the texture, color and chemical composition of the fruit. Semi-ripe avocados are aged for 5 days, while ripe avocados are aged for 8 days. This analysis uses a UV-Vis spectrophotometer with a maximum wavelength. The wavelength used is 575 nm. The results obtained in this study were that ripe fruit had higher carbohydrate levels compared to half-ripe fruit.